Kekaburan Norma Hukum Hubungan Industrial tentang Force Majeur Saat Menghadapi Kondisi Pandemi Covid 19 - Agus Salim Ra’is; Didik Suhariyanto; Ismail Ismail (Jurnal Syntax Admiration, 2024)
This study examines the ambiguity of legal norms related to industrial relations in the context of force majeure during the Covid-19 pandemic. The main focus is on the provisions of Law Number 13 of 2003 concerning Manpower and Law Number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation, which regulates termination of employment (PHK) and force majeure conditions. It was found that force majeure provisions that have not undergone changes or revisions in the latest law have caused legal uncertainty, allowing employers to carry out unilateral layoffs without the obligation to pay severance pay. This ambiguity of norms results in violations of the principles of legality, legal certainty, and utility, and has a negative impact on labor protection, especially in crisis situations such as the pandemic.